2023
DOI: 10.3847/1538-4357/acafe1
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Disruption Events from Eccentric Orbits and Lessons Learned from the Noteworthy ASASSN-14ko

Abstract: Stars grazing supermassive black holes (SMBHs) on bound orbits may survive tidal disruption, causing periodic flares. Inspired by the recent discovery of the periodic nuclear transient ASASSN-14ko, a promising candidate for a repeating tidal disruption event (TDE), we study the tidal deformation of stars approaching SMBHs on eccentric orbits. With both analytical and hydrodynamic methods, we show the overall tidal deformation of a star is similar to that in a parabolic orbit provided that the eccentricity is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 102 publications
1
3
0
Order By: Relevance
“…provide conclusive evidence for a repeated pTDE classification, which might occur in the next couple of years. We notice that recent simulation works of repeated pTDEs (e.g., Bandopadhyay et al 2024;C. Liu et al 2024) have reproduced the light-curve patterns similar as ASASSN-14ko, AT 2020vdq, and AT 2022dbl under several sets of stellar parameters (e.g., mass and age) and β.…”
Section: Robustness Of a "Repeated Ptde" Classificationsupporting
confidence: 65%
“…provide conclusive evidence for a repeated pTDE classification, which might occur in the next couple of years. We notice that recent simulation works of repeated pTDEs (e.g., Bandopadhyay et al 2024;C. Liu et al 2024) have reproduced the light-curve patterns similar as ASASSN-14ko, AT 2020vdq, and AT 2022dbl under several sets of stellar parameters (e.g., mass and age) and β.…”
Section: Robustness Of a "Repeated Ptde" Classificationsupporting
confidence: 65%
“…In contrast to the singlepassage TDEs, in an eccentric tidal stripping, the star will undergo many pericenter passages. Eccentric Tidal stripping of a giant star and a solar-type star are studied in MacLeod et al (2013) and Liu et al (2023), respectively. For the tidal stripping of a WD, Cheng & Evans (2013) explored the relativistic effects in the tidal interaction.…”
Section: Introductionmentioning
confidence: 99%
“…If the star can survive the approach, it could exhibit periodic outbursts (MacLeod et al 2013;Nixon & Coughlin 2022). In Liu et al (2023) the authors showed that stars on highly eccentric orbits can produce multiple, short-lived TDEs compared to parabolic encounters, which may explain peculiar, repeating TDEs like ASASSN-14ko.…”
Section: Introductionmentioning
confidence: 99%
“…Many optical observations were produced by large surveys, like the Sloan Digitized Sky Survey (SDSS) (e.g., Komossa et al 2008;Wang et al 2011;van Velzen et al 2011;Wang et al 2012;Yang et al 2013) or the Zwicky Transient Facility (ZTF) (van Velzen et al 2019a(van Velzen et al , 2021. For fitting the light curve of a TDE many authors used the popular open source MOSFiT code (e.g., Mockler et al 2019;Nicholl et al 2020;Liu et al 2023).…”
Section: Introductionmentioning
confidence: 99%